1993
DOI: 10.1007/bf00016333
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in biological nitrogen fixation by common bean

Abstract: Field experiments were performed in Austria, Brazil, Chile, Colombia, Guatemala, Mexico and Peru as part of an F A O / I A E A Co-ordinated Research Programme to investigate the nitrogen fixing potential of cultivars and breeding lines of common bean (Phaseolus vulgaris L.). Each experiment included approximately 20 bean genotypes which were compared using the 15N isotope dilution method. Great differences in nitrogen fixation were observed between and within experiments, with average values of 35% N derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 5 publications
2
27
0
2
Order By: Relevance
“…In a previous study, Franzini et al (2013) demonstrated that Aporé and Ouro Negro yielded similar GDW values in an experiment with low (2.2 mg N kg -1 soil) and high N content in the soil (200 mg N kg -1 soil). The values of %Ndfa found in this study were comparable to the values reported by Hardarson et al (1993), who observed 70% Ndfa in common beans grown in a field under favorable environmental conditions. Similarly, Rondon et al (2007) showed values from 50 to 72%.…”
Section: Cultivarsupporting
confidence: 80%
See 1 more Smart Citation
“…In a previous study, Franzini et al (2013) demonstrated that Aporé and Ouro Negro yielded similar GDW values in an experiment with low (2.2 mg N kg -1 soil) and high N content in the soil (200 mg N kg -1 soil). The values of %Ndfa found in this study were comparable to the values reported by Hardarson et al (1993), who observed 70% Ndfa in common beans grown in a field under favorable environmental conditions. Similarly, Rondon et al (2007) showed values from 50 to 72%.…”
Section: Cultivarsupporting
confidence: 80%
“…Nevertheless, some studies indicate that indigenous rhizobia strains are not efficient in common bean BNF, and these strains could hinder the introduction of more efficient strains (Vieira, 1998a), which is usually attributed to the lack of competitiveness against indigenous rhizobia, environmental conditions and plant genetic factors (Piha & Munns, 1987;Hardarson et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Houve redução da massa de nódulos, entre os estádios de floração e início de enchimento de vagens, de 73 para 54 mg por planta, respectivamente (Figura 1), o que denota um processo de senescência de nódulos nos estádios reprodutivos, que está associado à menor aquisição de N simbiótico pelo feijoeiro (Piha & Munns, 1987). Todavia, as quantidades de N oriundos da simbiose podem representar um aporte expressivo de N para o feijoeiro (Hardarson et al, 1993), que pode assumir ainda maior relevância em sistemas orgânicos de produção, em que a menor disponibilidade de nutrientes oriunda da mineralização dos fertilizantes orgânicos pode reduzir o rendimento dos cultivos em algumas situações (Sacco et al, 2015). Graham et al (2003) relacionaram alguns caracteres com potencial para a seleção de genótipos de feijoeiro, com maior contribuição do N oriundo da simbiose, tais como massa de nódulos, duração do período de fixação de N, retardamento da senescência nodular, alta acumulação de massa de matéria e de N da parte aérea.…”
Section: Resultsunclassified
“…The nitrogen fertilizers use is indicated in some situations to achieve good yields, even though they may affect negativity the BNF efficiency. Mean values of 35% and maximum of 70% of N derived from the atmosphere were observed at the plant biomass considering six field experiments in tropical countries and Austria [88]. Some progress is occurring with the best selection of strains, adapted to the conditions of each site [89][90][91][92].…”
Section: Beansmentioning
confidence: 99%